POLISEMIYA HÁM OMONIMLERDIŃ ULÍWMALÍQ BELGILERI HÁM ÓZGEShELIKLERI - Orazımbetov, A.Q. (SCIENCE and SOCIETY, 2025)
The article examines modern linguistics’ approaches to the phenomenon of polysemy and homonymy at different levels of the language system.
Keywords: polysemy; homonymy; metaphor; lexical-semantic variants of words; multiple meanings; word formation